Ferroptosis-associated circular RNAs: Opportunities and challenges in the diagnosis and treatment of cancer - Ruotong Yang; Ruotong Yang; Liwei Ma; Liwei Ma; Junhu Wan; Junhu Wan; Zhuofang Li; Zhuofang Li; Zhengwu Yang; Zhengwu Yang; Zhuochen Zhao; Zhuochen Zhao; et al. (Frontiers in Cell and Developmental Biology, 2023)
Ferroptosis is an emerging form of non-apoptotic regulated cell death which is different from cell death mechanisms such as autophagy, apoptosis and necrosis. It is characterized by iron-dependent lipid peroxide accumulation. Circular RNA (circRNA) is a newly studied evolutionarily conserved type of non-coding RNA with a covalent closed-loop structure. It exhibits universality, conservatism, stability and particularity. At present, the functions that have been studied and found include microRNA sponge, protein scaffold, transcription regulation, translation and production of peptides, etc. CircRNA can be used as a biomarker of tumors and is a hotspot in RNA biology research. Studies have shown that ferroptosis can participate in tumor regulation through the circRNA molecular pathway and then affect cancer progression, which may become a direction of cancer diagnosis and treatment in the future. This paper reviews the molecular biological mechanism of ferroptosis and the role of circular RNA in tumors and summarizes the circRNA related to ferroptosis in tumors, which may inspire research prospects for the precise prevention and treatment of cancer in the future.